Biodiversity conservation in a fragmented landscape : arthropod assemblages in smaller corridors within a production landscape - Van Schalkwyk, Julia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.